Of Histories, Erasures and the Beloved: Glimpses into Philippine Contemporary Poetry - Roma, De La Salle University, Manila, Dinah (Asiatic: IIUM Journal of English Language and Literature, 2015)
To attempt a definition of Philippine contemporary poetry is to confront its historical and literary legacies and upheavals. While it has already been said that the Philippine writing in English is one of the most expansive in Southeast Asia, this assessment remains but a strand in the countryâ€™s remarkably diverse literary milieu. There is much to be explored in the writings in FilipinoÂ â€”however the term may be contentious in embodying the regional languages that many of the countryâ€™s writers are now advocating so as to affirm national identity. At the same time, the American literary landscape continues to dominate the poetics of many young writers as they destabilise long held creative practices. Â Â This essay does not aim to map a cross-section of todayâ€™s poetic production. What it offers are glimpses of the bursting energies that propel the writings among contemporary poets. Charlie Veric Samuyaâ€™sÂ HistoriesÂ (2015), Mesandel Arguellesâ€™sÂ PesoaÂ (2014), and Genevieve Asenjoâ€™s bilingual collectionÂ Sa Gihapon, Palangga, An UranÂ (2014) are recent releases in English, Filipino, and Kinaray-a. The three languages give a sampling of the richness of Philippine literature in general. As individual works that mark various points in the three writersâ€™ career, they impress by the strategies through which they execute their poetic projects. What this essay further offers is a sense of the other voices out there simply waiting to be heard.